2018
DOI: 10.1055/s-0038-1670677
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded Protein Response Sensors in Hepatic Lipid Metabolism and Nonalcoholic Fatty Liver Disease

Abstract: Activation of the hepatic unfolded protein response (UPR), a highly conserved cellular response to endoplasmic reticulum (ER) stress, is a firmly established feature of nonalcoholic fatty liver disease (NAFLD). ER stress is now widely accepted as both a cause and a consequence of hepatic steatosis. Moreover, the accumulation of hepatic lipids induces ER stress, which, in turn, disrupts hepatic lipid metabolism thus creating a vicious cycle that potentiates hepatic lipid accumulation. Additionally, there is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 158 publications
1
18
0
1
Order By: Relevance
“…Under unstressed conditions, IRE1, PERK, and ATF6 are associated with GRP78 and remain inactive. Upon ER stress, GRP78 dissociates from these sensor proteins, and further actives PERK and IRE1, and regulates intramembrane proteolysis of ATF6 (As, 2018). In this study, after 4 weeks of PA administration, the increased levels of ROS and MDA were markedly decreased in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under unstressed conditions, IRE1, PERK, and ATF6 are associated with GRP78 and remain inactive. Upon ER stress, GRP78 dissociates from these sensor proteins, and further actives PERK and IRE1, and regulates intramembrane proteolysis of ATF6 (As, 2018). In this study, after 4 weeks of PA administration, the increased levels of ROS and MDA were markedly decreased in HFD-fed rats.…”
Section: Discussionmentioning
confidence: 99%
“…Very low-density lipoprotein (VLDL) metabolism is considered as a beneficial factor in overcoming the excess formation of triglyceride (TG) and regulating intrahepatic and plasma lipid homeostasis. A dysregulation in VLDL uptake, export, or synthesis is one of the major causes of hepatic steatosis (As, 2018). Current studies have demonstrated that endoplasmic reticulum (ER) stress is implicated in the inhibition of VLDL metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic ER stress, induced by pharmacological agents or metabolic dysregulation, promotes hepatic lipid accumulation by increasing lipogenesis (32). Genetic ablation studies revealed that the phosphorylation of eIF2α, a key downstream target of PERK, exacerbates the progression of hepatic steatosis in mice subjected to pharmacologically induced ER stress (33).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]21 Although the association between metabolic disease and induction of PAI-1 is well-established, the mechanism by which metabolic derangements induce PAI-1 is unknown. Given that induction of hepatic ER stress is a well-recognized feature of NASH, 22 we considered whether ER stress contributes to the characteristic induction of PAI-1 in NASH. Therefore, in the present study we aim to (a) determine the role of ER stress in the regulation of hepatic Pai-1 expression and (b) determine whether induction of Pai-1 in a murine model of steatohepatitis is regulated by ER stress.…”
mentioning
confidence: 99%